Sagas and Secularity: The (Re)Construction of Secular Literature in 20th-century Iceland - Hreinsson, Haraldur (2022)
The study of secularity in Iceland has so far largely been restricted to institutional differentiation, alongside legal aspects of the relationship between the state and the country’s national church. This paper approaches the formation of secularity in the country from a different angle. Adopting a research perspective shaped by both cultural history and sociology of culture, it investigates the role of the Icelandic sagas, and the medieval culture which spawned them, in the development of secularity in Iceland. Instead of looking at the processes through which Christian religion came to be separated from other spheres of society, it probes the discourses legitimising such a separation. It pays special attention to the reception and understanding of the sagas and the medieval culture which produced them, and further asks how they provided a background against which a secular culture could be imagined, both in the past and for the present.